Spousal Violence and Social Norms in India's North East - Sumantra Pal (ZBW – Leibniz Information Centre for Economics, 2018)
A body of extant literature suggests that improvements in wellbeing and empowerment of women in the process of development are hindered by traditional social norms, which are often patriarchic. This paper investigates the link between traditional social norms and women's status, in particular, the women's attitude towards violence and incidence of spousal violence. The study context is the tribes of Meghalaya and neighboring areas, where there is great variation regarding patriarchic versus matriarchic lineage, residence and inheritance customs. For the statistical analysis, we combine information on social norms prevailing among the different tribes from the comprehensive ethnographic atlas People of India with household-level data from the National Family Health Survey (NFHS). In addition to individual characteristics, we find the extent to which social norms determine violence against women and under what prevailing norms working women are better-off.
Keywords: Z13; B54; J12; 330; Social Norms; Spousal Violence